The Influence of Work Experience on Work Productivity with Job Satisfaction as Mediator - Joko Muji Subagyo; Deni Widyo Prasetyo; Wasis Wasis (International Journal of Management Science and Application, 2023)
Tofu is one of the most famous processed soybean food products in Indonesia. Research Object of the Z Tofu Factory in Jombang Regency. The problem with the Z tofu factory is that the raw materials produced for making products do not all become finished tofu products, every month there are always damaged products from the production output, this shows that employee productivity is not yet optimal. The sample used in this research used saturated sampling, namely all employees in the production section at the tofu factory, totalling 45 employees. Data analysis uses path analysis with SPSS. The research results explain that there is a significant positive influence of work experience on job satisfaction, meaning that the more employees have more experience at work, the more satisfied employees are in their work. There is a significant positive influence of work experience on employee work productivity, meaning that the more experience the employee has at work, the higher the employee's work productivity. There is a significant positive influence of job satisfaction on employee work productivity, meaning that if employees feel satisfied with their work, employee work productivity will increase. Job satisfaction is an intervening or mediating variable between work experience and employee work productivity. The findings in this research are that employee experience of more than 5 years is able to provide satisfaction with work results so that it can increase work productivity. The conclusion of this research is that work experience has a positive effect on job satisfaction, work experience has a positive effect on work productivity, job satisfaction has a positive effect on work productivity, job satisfaction is a mediator between work experience and employee work productivity.